Ni-BASED ALLOY HAVING EXCELLENT SURFACE PROPERTIES
Patent Information
- Application Number
- JP2023137237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-25
AI Technical Summary
【0023】 さらに、前記記載のMgO単体はAl2O3:3%以下、SiO2:1%以下、CaO:10%以下、MnO:1%以下を含有すると良い。
Smart Images

Figure 2025031188000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Ni-Cr-Mo-W-Fe system Ni-based alloy having excellent surface properties and a method for producing the same. [Background technology]
[0002] Ni-based alloys, which have excellent corrosion and acid resistance, contain Cr, Mo, and W in addition to the main component Ni, and since these metals are extremely expensive compared to iron, it is extremely important to improve yield and reduce manufacturing costs. However, if surface defects such as linear scratches occur on the surface of Ni-based alloys, they not only do not exhibit the required corrosion resistance, but also impede weldability, creating many other issues. Furthermore, since the defective areas significantly reduce the yield, there was a demand for Ni-based alloys with excellent surface properties.
[0003] Patent Document 1 discloses a technique for improving surface properties by carefully controlling the composition of nonmetallic inclusions in a Ni-based alloy. However, depending on the structure of the nonmetallic inclusions, defects are not necessarily eliminated, and this technique poses a technical problem.
[0004] Patent Document 2 discloses a method for refining a Ni-based alloy. However, the structure of nonmetallic inclusions is not examined.
[0005] Patent Document 3 discloses a technique for surface treatment of Ni-based alloys. It explains that corrosion resistance can be improved by making the passive film appropriate. However, no technical development has been done regarding surface defects.
[0006] In fact, Ni-based alloys containing large amounts of Ni, Cr, Mo, W, etc. and having improved corrosion resistance and acid resistance are widely used in flue gas desulfurization equipment used on ships and thermal power plants, which is used in harsh sulfuric acid environments. In recent years, the demand for Ni-based alloys has been increasing as environmental regulations regarding ship exhaust gases have become stricter. Furthermore, the importance of nuclear power generation has been pointed out from the perspective of carbon neutrality, and it is expected that the use of Ni-based alloys will continue to expand in the future.
[0007] Patent Document 4 discloses a technology for improving stainless steel for use in nuclear power plants. In recent years, in harsh operating environments, Ni-based alloys are required for the inside of nuclear power pressure vessels, although this depends on the location.
[0008] Patent Documents 5 and 6 present techniques related to Ni-based alloy products intended for use as reactor structural members in a high-temperature water environment for a long period of time. However, the problem of surface defects was not resolved. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 6990337 [Patent Document 2] JP 2009-114544 A [Patent Document 3] JP 2015-183290 A [Patent Document 4] Special Publication No. 35-16661 [Patent Document 5] Patent No. 4340899 [Patent Document 6] Patent No. 4433230 Summary of the Invention [Problem to be solved by the invention]
[0010] As described above, the main aim of the present invention is to prevent the clustering of nonmetallic inclusions, which can cause large surface defects, by controlling not only the composition of the nonmetallic inclusions but also their structure. At the same time, the formation of CaO inclusions and Al2O3 inclusions must be prevented because they tend to cluster. Furthermore, MnO-Cr2O3 inclusions are formed in an environment with a high oxygen concentration, so the total number of inclusions is large and they are also prone to clustering, so they must be prevented.
[0011] That is, an object of the present invention is to comprehensively consider the above and to provide a Ni-based alloy having a defect-free and good surface quality, and a method for producing the same. [Means for solving the problem]
[0012] In order to solve the problems of the above-mentioned conventional techniques, the inventors have repeatedly carried out intensive experiments as described below.
[0013] First, 20 kg of Ni-16%Cr-16%Mo-3%W-6%Fe alloy was melted in a magnesia crucible in the laboratory. A high-frequency induction furnace was used as the melting equipment, and argon gas was blown from above the crucible to isolate it from the atmosphere. The raw materials used were electrolytic iron, ferrochrome, Mo, copper wire, and W. Finally, Si and Al were added to deoxidize the alloy, and 1 kg of artificial slag of CaO-Al2O3-MgO-SiO2-F system was added, and the composition of the nonmetallic inclusions was carefully observed by sampling. The observation was performed using SEM. The analysis was performed using EDS. In particular, elemental mapping was performed carefully, and the structural morphology was carefully observed. It was found that at least 10 points of the inclusions need to be analyzed to find the compositional characteristics, 20 points is better, and 30 points or more is sufficient.
[0014] The Ni-based alloy ingot cast into the mold was forged to a thickness of 20 mm, after which the surface was ground and cold rolled. The final plate thickness was 0.5 mm, and the surface was carefully observed to determine whether there were any defects.
[0015] As a result, it was found that the occurrence of defects is strongly related to the structural morphology of nonmetallic inclusions, and that a structural morphology in which CaO-Al2O3-MgO oxides contain MgO or MgO·Al2O3 has a high ability to suppress clustering. A schematic diagram of this is shown in Figure 1. Figure 1(a) shows a CaO-Al2O3-MgO oxide that completely contains MgO or MgO·Al2O3 within its approximately spherical surface, which is a good morphology that can suppress clustering. On the other hand, as shown in Figure 1(b), it was revealed that a morphology in which part of the outer edge is CaO-Al2O3-MgO, and most of the inside is high-melting point MgO or MgO·Al2O3 oxide that protrudes from the approximately spherical surface of the inclusion promotes clustering. Although the mechanism is largely unknown, it is assumed that the CaO-Al2O3-MgO melt acts as a sintering aid at the so-called refining temperature (1400-1550℃), adhering to each other and sintering. Based on experience, it has been assumed that the main sintering location is the inner wall of the submerged nozzle of the continuous casting machine.
[0016] On the other hand, it was also confirmed that sintering does not occur when MgO·Al2O3 or MgO is used alone. It became clear that the structure of the surrounding CaO-Al2O3-MgO oxide melt has a large effect on the final quality.
[0017] With this, the raw materials for some alloy types were melted in a 70-ton electric furnace, decarburized in an AOD, quicklime was added from above while FeSi was added at the same time, Cr reduction was performed, and then Al was added to proceed with deoxidization and desulfurization for refinement. Slabs were then produced in a continuous casting machine, and after surface grinding, they were hot rolled, cold rolled, and finally passed through an annealing and pickling line to produce 0.5 mm thick thin plates. The surfaces were observed with the naked eye to study the presence or absence of surface defects.
[0018] That is, the present invention was developed based on the above laboratory studies and through confirmation by actual equipment testing, as described below.
[0019] The chemical compositions are all in mass percent: C: 0.001-0.1%, Si: 0.01-0.4%, Mn: 0.1-1%, P: 0.03% or less, S: 0.002% or less, Cr: 13-35%, Mo: 18% or less, W: 5% or less, Cu: 1% or less, Al: 0.001-0.35%, Ti: 0.001-0.2%, Ca: 0.0001-0.02%, Mg: 0.0001-0. It is a Ni-based alloy containing 0.02%, N: 0.001-0.03%, Fe: 2-11%, O: 0.005% or less, 4% or less of one or more of Co, Nb, and B, with the balance being Ni and unavoidable impurities, and the average composition of non-metallic inclusions is MgO: 30-70%, Al2O3: 15-40%, SiO2: 30% or less, CaO: 10-40%, and MnO: 1% or less.
[0020] In the Ni-based alloy of the present invention, the structural form of the nonmetallic inclusions is more preferably such that 70% or more of the nonmetallic inclusions in terms of number ratio to the total nonmetallic inclusions are any one or more of the following five types a to e. a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone
[0021] In addition, the CaO-Al2O3-MgO-based oxide described above preferably has a composition of CaO: 20-60%, Al2O3: 30-60%, MgO: 1-30%, SiO2: 20% or less, and TiO2: 0.5% or less.
[0022] Here, it is preferable that the above-mentioned MgO·Al2O3 contains 0.5% or less of MnO.
[0023] Furthermore, it is preferable that the simple substance of MgO described above contains Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.
[0024] The present invention also provides a manufacturing method, which is a method for manufacturing a Ni-based alloy, in which raw materials are melted in an electric furnace, then decarburized and refined in an AOD, and one or more of quicklime, magnesia-containing waste bricks, fluorite, ferrosilicon alloy, Si, and Al are added to perform Cr reduction, and Al is further added to form CaO-Al2O3-MgO-SiO2-F slag, which is deoxidized and desulfurized, and then a slab is produced in a continuous casting machine, and the surface is ground, followed by a hot rolling process and a cold rolling process. [Brief description of the drawings]
[0025]
Figure 1
Figure 2
[0026] The reasons for the numerical limitations of the present invention and the scientific viewpoints thereof will be explained below. The units below are % by mass. C: 0.001 to 0.1% C is an important element for maintaining the strength of Ni-based alloys and for improving wear resistance by forming carbides with Cr. Therefore, 0.001% is necessary. On the other hand, adding more than 0.1% has the drawback of forming carbides of Ti, Nb, etc., which leads to embrittlement. Therefore, the content is specified as 0.001 to 0.1%. The addition is controlled by adding pig iron after desulfurization in the AOD. The content is preferably 0.002 to 0.09%, and more preferably 0.005 to 0.07%.
[0027] Silicon: 0.01 to 0.4% In addition to being effective in deoxidation, silicon is an element that improves heat resistance and is very important in the present invention. Deoxidation can be carried out according to the following formula. In other words, in AOD, FeSi alloy is added to the Cr reduction. Si +2 O =(SiO2) …(1) Here, the underlined parts are the components in the molten alloy, and the parentheses are the components in the slag. As will be described later, by lowering the activity coefficient of SiO2 in the slag, deoxidation can be effectively promoted and the oxygen concentration can be controlled to the oxygen concentration of the present invention. Furthermore, desulfurization can be performed at the same time. 0.01% is necessary to achieve this effect, and if it exceeds 0.4%, it will not only form a σ phase, which reduces the corrosion resistance, but will also cause embrittlement. Therefore, the content is specified to be 0.01 to 0.4%. It is preferably 0.02 to 0.38%, and more preferably 0.02 to 0.37%.
[0028] Mn: 0.1-1% Mn is an effective element for deoxidization, and therefore, its content is specified to be 0.1 to 1%, preferably 0.2 to 0.9%, and more preferably 0.3 to 0.8%.
[0029] P:0.03% or less P is a harmful element that not only segregates at grain boundaries and reduces corrosion resistance, but also causes red brittleness during welding, leading to cracking. Therefore, the P content is set to 0.03% or less, preferably 0.028% or less, and more preferably 0.025% or less.
[0030] S: 0.002% or less S is a harmful element because it segregates at grain boundaries and forms MnS, which becomes the starting point of pitting corrosion. It also reduces hot workability and causes edge cracks. Therefore, the content is set at 0.002% or less. As will be explained in detail later, desulfurization can be promoted by the following reaction formula. 3(CaO)+2 Al +3 S =(Al2O3)+3(CaS) …(2) 2(CaO)+ Si +2 S =(SiO2)+2(CaS) …(3) The desulfurization reaction can be promoted efficiently by reducing the activity coefficient of alumina and silica in the slag. If the activity coefficient is 0.002% or less, the above problems can be avoided, so the range is specified as above. The content is preferably 0.0018% or less, more preferably 0.0017% or less, and even more preferably 0.0015% or less.
[0031] Cr: 13~35% Cr is a major element in the present invention, and is essential for forming a dense passive film on the surface of the Ni-based alloy to maintain corrosion resistance. Therefore, the content is specified to be 13 to 35%. It is preferably 14 to 34%, more preferably 14.5 to 33%, and even more preferably 15 to 32.5%.
[0032] Mo: 18% or less Mo is an important element in the present invention. It plays a role in retarding the progression of pitting corrosion and improving corrosion resistance. However, if the content is too high, it forms intermetallic compounds and causes embrittlement. Therefore, the content is specified to be 18% or less. It is preferably 17% or less, and more preferably 16% or less. It is also desirable for the content to be 0.5% or more. Furthermore, it is even more desirable for the content to be 2% or more.
[0033] W: 5% or less W is an important element in the present invention. It plays a role in slowing down the progression of pitting corrosion and improving corrosion resistance. However, if the content is too high, it forms intermetallic compounds and causes embrittlement. Therefore, the content is specified to be 5% or less. It is preferably 4.5% or less, and more preferably 4.2% or less. It is also desirable to have a content of 0.5% or more. Furthermore, it is even more desirable to have a content of 2% or more.
[0034] Cu: 1% or less Cu is an important element for improving acid resistance and sulfuric acid resistance, and for maintaining corrosion resistance. It also has the effect of softening in cold working, making it an extremely important element for deep drawing applications. However, if the Cu content is too high, the Ni-based alloy will soften. Therefore, the Cu content is set at 1% or less. It is preferably 0.9% or less, and more preferably 0.6% or less. It is also desirable for the Cu content to be 0.01% or more.
[0035] Al: 0.001 to 0.35% Al is a useful element for deoxidation. It also improves high-temperature oxidation resistance. On the other hand, if the content is too high, AlN is formed, impairing hot workability, and the Ca and Mg concentrations become too high, exceeding the upper limit of the range of the present invention. As a result, harmful CaO-based inclusions are formed, and a low-melting point compound called NiMg2 is formed, reducing hot workability. The deoxidation reaction proceeds as follows. 2 Al +3 O =(Al2O3) … (4) As will be described in detail later, by lowering the alumina activity in the slag, deoxidation proceeds efficiently. Furthermore, desulfurization also becomes possible at the same time. Therefore, the content is specified to be 0.001 to 0.35%. It is preferably 0.005 to 0.3%, more preferably 0.007 to 0.28%, and further preferably 0.01 to 0.25%.
[0036] Ti: 0.001 to 0.2% Ti has the effect of fixing N in the form of TiN and preventing blowholes caused by nitrogen gas emission during solidification. However, if the Ti content is too high, not only will there be too much TiN, but TiC will also be formed, causing surface defects. Therefore, the Ti content is specified to be in the range of 0.001 to 0.2%, preferably 0.002 to 0.1%, and more preferably 0.002 to 0.05%.
[0037] Ca: 0.0001-0.02% Ca is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxides. By controlling the structure in this way, it is possible to manufacture sound products without clustering or forming surface defects. Ca is effectively added by utilizing the following reaction: 3(CaO)+2 Al =(Al2O3)+3 Ca …(5) 2(CaO)+ Si =(SiO2)+2 Ca …(6) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if the content is too high, harmful CaO inclusions are formed, which promotes clustering and forms defects. Therefore, the content is specified to be 0.0001 to 0.02%. It is preferably 0.0003 to 0.018%, and more preferably 0.0005 to 0.015%. It is further preferably 0.0006 to 0.01%.
[0038] Mg: 0.0001-0.02% Mg is an important element for controlling the structure of nonmetallic inclusions to the preferred CaO-Al2O3-MgO oxide, MgO, and MgO·Al2O3. By controlling the structure in this way, it is possible to manufacture sound products without clustering or forming surface defects. Mg is effectively added by utilizing the following reaction: 3(MgO)+2 Al =(Al2O3)+3 Mg …(7) 2(MgO)+ Si =(SiO2)+2 Mg …(8) To control this reaction, the activity of alumina and silica in the slag should be controlled within an appropriate range. This will be explained in detail in the manufacturing method. On the other hand, if it is too high, Mg vaporizes during solidification and forms blowholes, which in turn form surface defects. Therefore, the content is specified to be 0.0001 to 0.02%. It is preferably 0.0005 to 0.018%, and more preferably 0.001 to 0.015%.
[0039] Fe: 2-11% Fe is an important element for maintaining strength by dissolving in Ni-based alloys. It also allows the use of ferroalloys as a raw material, which reduces costs. However, if the content is too high, it reduces corrosion resistance. Therefore, it is specified to be 2 to 11%. It is preferably 3 to 10.5%, and more preferably 4 to 10%.
[0040] N: 0.001 to 0.03% N is effective for maintaining strength by dissolving in Ni-based alloys, and also plays a role in preventing pitting corrosion by providing NH4Cl to pitting corrosion. Therefore, the range of N content is set to 0.001 to 0.03%, preferably 0.002 to 0.028%, and more preferably 0.008 to 0.025%.
[0041] O: 0.005% or less The oxygen content must be reduced because it increases the number of nonmetallic inclusions and forms surface defects. Therefore, the oxygen content is set to 0.005% or less. It is preferably 0.003% or less, more preferably 0.002% or less, and even more preferably 0.001% or less.
[0042] One or more of Co, Nb, and B should be 4% or less Co is an effective element because it behaves in the same way as Ni. It is also sometimes included in pure Ni raw materials, and plays an important role in terms of utilizing inexpensive raw materials. Nb is beneficial for maintaining strength through solid solution. B improves hot workability. It is more preferable to include one or more of these elements at 4% or less. In other words, they may be added as necessary.
[0043] The balance of the Ni-based alloy of the present invention is Ni. In addition, it may contain trace amounts of unavoidable impurities such as Pb, Sn, Ta, Ag, Na, K, and Zr. All of these are mixed in from the scraps that are the raw materials.
[0044] Next, the average composition of the nonmetallic inclusions will be described. The average composition of the nonmetallic inclusions is as follows: MgO: 30~70% MgO is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming simple MgO and simple MgO·Al2O3, which are similarly harmless. Therefore, the content is specified to be 30 to 70%. The preferred content is 35 to 65%.
[0045] Al2O3: 15-40% Al2O3 is effective for forming harmless CaO-Al2O3-MgO oxides, and is also extremely effective for forming MgO·Al2O3, which is also harmless. However, if it is higher than 40%, it forms harmful Al2O3 simple substance, which causes defects. Therefore, it is specified to be 15-40%. It is preferably 18-39%.
[0046] SiO2: 30% or less SiO2 is a compound present in CaO-Al2O3-MgO oxides, and is effective in lowering the melting point. However, if it exceeds 30%, it acts in the direction of increasing the oxygen concentration, which not only increases the number of nonmetallic inclusions but also forms harmful MnO-Cr2O3 oxides, resulting in defects. Therefore, it is specified to be 30% or less. Preferably, it is 28% or less.
[0047] CaO: 10-40% CaO is effective for forming harmless CaO-Al2O3-MgO oxides, but if the content is too high, harmful CaO inclusions are formed, resulting in defects. Therefore, the content is specified to be 10 to 40%. The content is preferably 12 to 39%. The content is more preferably 13 to 38%.
[0048] MnO: 1% or less MnO is harmless because it dissolves in the MgO sites of MgO and MgO·Al2O3 inclusions. However, if the content is too high, it forms harmful MnO-Cr2O3 oxides, which can cause defects. Therefore, the content is set at 1% or less. It is preferably 0.9% or less. It is more preferably 0.8% or less.
[0049] Cr2O3: 1.5% or less Although not particularly limited, a high Cr2O3 content makes it easier for MnO-Cr2O3-based inclusions to form. Furthermore, the oxygen concentration in the molten alloy also increases, increasing the number of nonmetallic inclusions and causing defects. Therefore, it is preferable that the Cr2O3 content is 1.5% or less. More preferably, it is 1.3% or less. Even more preferably, it is 0.6% or less.
[0050] There are several methods for determining the average composition. It can be clarified by randomly analyzing 10 points using SEM / EDS. In this case, it is necessary to analyze two points on the periphery of the center, and the average can be obtained by taking a mapping and measuring the area ratio by image analysis. It is preferable to analyze 20 points or more, and more preferably 30 points or more. The other is the so-called electrolytic method, which is widely known as the Speed method. In other words, the metal part is dissolved by applying an appropriate potential in an appropriate solution. After that, the non-metallic inclusions that become the residue are collected by filtration. The average composition can be obtained all at once by subjecting this to chemical analysis. There is no limitation on the analysis method.
[0051] Furthermore, the structural morphology of nonmetallic inclusions will be explained. In a more preferred embodiment, nonmetallic inclusions that account for 70% or more of the total number of nonmetallic inclusions are one or more of the following five types a to e. The structural morphologies corresponding to a to e are also shown in Figures 2(a) to (e). a: CaO-Al2O3-MgO oxide completely encloses MgO·Al2O3 within a roughly spherical surface b: CaO-Al2O3-MgO oxide c: CaO-Al2O3-MgO oxide completely encloses MgO within a roughly spherical surface d: MgO alone e: MgO·Al2O3 alone Here, being completely contained within an approximately spherical surface means that the internal material is completely contained within the material on the outer edge as shown in FIG. 1(a), and does not include a state in which the internal material partially protrudes to the outside as shown in FIG. 1(b).
[0052] As explained in the means for solving the problems, the form in FIG. 1(b) does not appear in the following operation. In order to control these structural forms, it is sufficient to control the chemical components Si, Al, Ca, Mg, O, and Mn within the range of the present invention, but this is not all. a and c are also characteristic of the present invention. In order to achieve these structural forms, the key points are after the decarburization process in AOD. During the Cr reduction period, quicklime is first added, and at the same time, fluorite and waste bricks containing MgO are added. After that, when ferrosilicon alloy and Al are added, Si and Al are added to the already formed molten slag. This directly reacts with CaO and MgO in the slag, and Ca and Mg can be effectively added.
[0053] Mg is supplied to the molten alloy in advance according to the reactions of equations (7) and (8). The reason for this is unclear, but the reaction of Ca is delayed. This dissolved Mg reacts first with the original non-metallic inclusions, silica and alumina, as shown below. 2 Mg +SiO2(inclusion)=2MgO(inclusion)+2 Si …(9) 3 Mg +Al2O3(inclusion) = 3MgO(inclusion) + 2 Al …(10) 2 Mg +4 Al + 4SiO2(inclusions) = 2MgO·Al2O3(inclusions) + 4 Si …(11) 3 Mg + 4Al2O3(inclusions) = MgO·Al2O3(inclusions) + 2 Al …(12) As shown in formulas (9) to (12) above, simple MgO and simple MgO·Al2O3 are formed initially. After that, Ca is supplied from the slag, and the Ca in the molten alloy reacts with the inclusions mentioned above, causing CaO-Al2O3-MgO oxides to form vigorously on the surface. These molten oxides then cover the simple MgO and simple MgO·Al2O3, rendering them harmless. In other words, they are molten and behave as harmless CaO-Al2O3-MgO inclusions. Therefore, if the non-metallic inclusions are spherical, they will behave as described above and will be harmless.
[0054] Furthermore, the composition range of the above CaO-Al2O3-MgO oxide will be explained. CaO: 20~60%, Al2O3: 30~60%, MgO: 1~30%, SiO2: 20% or less, TiO2: 0.5% or less The above ranges were set because they allow the molten state of CaO-Al2O3-MgO oxides to be maintained at the refining temperature, i.e., near 1500°C. If the CaO content is too high, harmful simple CaO inclusions will form, so CaO: 20-60% was specified. If the Al2O3 content is too high, simple Al2O3 will form, so Al2O3: 30-60% was specified. MgO is set to 1-30% in order to maintain the molten state. If the SiO2 content is too high, harmful MnO-Cr2O3 inclusions will form, so it is set to 20% or less. If TiO2 is 0.5% or less, it will maintain the molten state, so these were specified.
[0055] MnO concentration in MgO·Al2O3: 0.5% or less Since MnO dissolves in the MgO sites of MgO·Al2O3, it is possible to render MnO harmless. Therefore, the content is set at 0.5% or less.
[0056] MgO simple inclusions contain Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, MnO: 1% or less Since MgO inclusions are harmless, it is desirable for them to dissolve in the inclusions to some extent. Taking into account the solubility limit, the contents are set at Al2O3: 3% or less, SiO2: 1% or less, CaO: 10% or less, and MnO: 1% or less.
[0057] The present invention also provides a manufacturing method. That is, the raw materials are melted in an electric furnace, and then decarburized and refined in an AOD. The raw materials may be stainless steel scrap, Ni, ferronickel alloy, ferrosilicon alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, ferrochrome alloy, copper wire, etc., which may be blended according to the type of alloy to be used.
[0058] After the decarburization process is completed, the Cr in the molten alloy is oxidized to form Cr2O3, so quicklime and FeSi are added to carry out Cr reduction according to the following reaction: 2(Cr2O3)+3 Si =3(SiO2)+4 Cr …(13)
[0059] Furthermore, Al is added to form CaO-Al2O3-MgO-SiO2-F slag, which is then deoxidized and desulfurized, and a slab is produced in a continuous casting machine. After the surface is ground, the slab is subjected to a hot rolling process and then cold rolling. At this time, in order to control the structure of the nonmetallic inclusions to a desirable form, it is necessary to control the slag composition within an appropriate range.
[0060] The following range is desirable for CaO-Al2O3-MgO-SiO2-F slag. CaO: 35-70% The CaO concentration can be adjusted by adding quicklime. CaO has a tremendous effect on deoxidation and desulfurization. In other words, as shown in formulas (2) and (3), desulfurization is possible by making CaO exist stably as CaS in the slag. However, if the CaO concentration is higher than 70%, CaO inclusions are formed. Therefore, 35 to 70% is preferable. Preferably, it is 40 to 65%. More preferably, it is 50 to 63%.
[0061] Al2O3: 30% or less Al2O3 is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if it exceeds 30%, it creates Al2O3 simple inclusions and promotes clustering. Therefore, it is desirable to keep it at 30% or less. Preferably, it is 25% or less. More preferably, it is 22% or less.
[0062] MgO: 3~25% MgO is effective in making CaO-Al2O3-MgO-SiO2-F slag molten. On the other hand, if the MgO concentration is high, the Mg concentration in the molten alloy will be high, and Mg gas will be released during solidification, forming blowholes. Therefore, 3 to 25% is preferable. 5 to 20% is more preferable, and 7 to 15% is even more preferable.
[0063] SiO2: 3-32% SiO2 is effective for molten CaO-Al2O3-MgO-SiO2-F slag. On the other hand, if the SiO2 concentration is high, the oxygen concentration in the molten alloy will be high, and the nonmetallic inclusion composition will also be MnO-Cr2O3. As a result, surface defects will occur. Therefore, 3-32% is preferable. 5-30% is more preferable. 5-20% is even more preferable.
[0064] F: 0.5 to 10% F is added as fluorite. F is effective in molten CaO-Al2O3-MgO-SiO2-F slag. On the other hand, if the F concentration is high, it will corrode the AOD bricks and ladle bricks, shortening their lifespan. Therefore, 0.5 to 10% is preferable. 1 to 9% is more preferable.
[0065] Furthermore, it is desirable that the Cr2O3 and FeO concentrations are low. Cr2O3: 1% or less If the Cr2O3 concentration is high, the oxygen concentration will increase and cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is best to keep it at 1% or less. It is preferably 0.7% or less. It is more preferably 0.6% or less.
[0066] FeO: 1% or less If the FeO concentration is high, the oxygen concentration will increase and cause the formation of MnO-Cr2O3-based inclusions. Therefore, it is preferable that the FeO concentration is 1% or less. It is preferably 0.9% or less. It is more preferably 0.8% or less.
[0067] Furthermore, a high S concentration is desirable because it indicates that desulfurization has progressed normally. A concentration of 0.3% or more is desirable, and a concentration of 0.4% or more is even more desirable. EXAMPLES
[0068] The effectiveness of the present invention will be clarified by showing examples below. The raw materials were melted in a 70-ton electric furnace and then decarburized and refined in an AOD. The raw materials were special steel scrap, stainless steel scrap, pure Ni, ferrosilicon alloy, ferrosilicon alloy, iron scrap, Mo, Mo trioxide, ferromolybdenum alloy, ferroniobium alloy, ferrochrome alloy, tungsten, Ti, copper wire, etc., which were blended according to the target alloy type.
[0069] After the decarburization process was completed, the Cr2O3 that had been transferred to the slag was reduced. That is, quicklime and waste bricks containing magnesia, as well as fluorite, were added, and then Al was added. This reduced the Cr oxide in the slag, completing the Cr reduction process, which returns the valuable metal Cr to the molten alloy.
[0070] In addition, in some alloys, ferrosilicon alloy was added to finally form CaO-Al2O3-MgO-SiO2-F slag. Even when Al was not added, the impurity Al in the FeSi alloy was oxidized to supply alumina.
[0071] For some alloy types, Nb, Mo, C, Co, W, Cr, B, Ni, and other alloying elements were added here to precisely adjust the chemical composition. After deoxidization and desulfurization in this way, slabs of 200 mmt x 1200 mmw x 7 m length were produced using a continuous casting machine, and after grinding the oscillation marks on the surface, they were heated to 1100 to 1250 °C depending on the alloy type, and then went through a hot rolling process, and finally cold rolling was performed and passed through an annealing and pickling line. In this way, 1 mm cold rolled coils were produced for all alloy types.
[0072] At this time, the evaluation was carried out by the following methods. 1) Chemical composition: The surface of a 30mm diameter x 10mm high suction sample taken from the tundish of the continuous casting machine was ground with a grinder. Major elements were analyzed by fluorescent X-ray analysis. Some C and S were analyzed by the combustion method. N and O were also analyzed by the infrared absorption method. In some cases, H was also measured using a hydrogen analyzer. 2) Slag components: Slag was collected with an iron bar and crushed. This was then pressed into a cylindrical sample. The values of this sample were determined using X-ray fluorescence analysis. F was determined by chemical analysis. 3) Average composition of non-metallic inclusions: The above-mentioned suction sample was cut out, embedded in resin, and mirror-polished. This was then placed in an SEM for observation and quantitative analysis. Thirty inclusions of 5 μm or more were randomly selected, and the center and periphery were analyzed. The element distribution of each inclusion was determined by mapping, and the ratio of each phase was calculated by image analysis. Taking into account the weighted average, a representative analysis value of each inclusion particle was obtained. This was determined by calculating the average value of the 30 points. 4) Morphology of nonmetallic inclusions: The morphology was classified when observed and analyzed as described above. The morphology shown in Figure 1(b) was not confirmed. 5) Composition of each oxide: Calculated from the composition of each oxide phase described above. 6) Overall evaluation: An inspector visually evaluated a 1 mm thick Ni-based alloy plate when it was threaded. The evaluation results were determined as follows. The allowable range for not cutting the plate is 10 mm from the surface of the plate. 2 This means that there are up to three linear scratches of 1mm or more in length per unit area. Passed: No surface defects (100% non-defective product at time of shipment) Passed: Some surface defects occurred but within the required quality tolerance (95% pass rate). Pass: △ Surface defects occurred in some areas, but the product can be shipped after partial cutting (80% pass rate) Rejected: × Surface defects occurred along the entire length of the coil, and the coil was scrapped (0% defective product rate).
[0073] [Table 1]
[0074] [Table 2]
[0075] The structural morphologies of the examples are shown in Figures 2(a) to (e), and those of the comparative examples are shown in Figures 2(f) to (h). The total of the chemical components in the examples is less than 100% due to unavoidable impurities. Nos. 1 to 14 of the invention examples had chemical analysis within the range, and the slag composition also satisfied the desired range. As a result, the structural morphology of the non-metallic inclusions also satisfied the range of a to e. Ultimately, all of the products were judged to be acceptable.
[0076] However, in No.5, one alumina inclusion and one MnO-Cr2O3 inclusion were confirmed, so the evaluation was good. In No.8, one CaO inclusion was observed. Therefore, the evaluation was good. In No.10, the MnO and Cr2O3 concentrations in the slag were slightly high, and reduction was poor, so Al2O3 inclusions and MnO-Cr2O3 inclusions were confirmed. Therefore, the evaluation was good. Furthermore, in No.11, the MnO concentration in the MgO·Al2O3 was high, and the SiO2 and MnO in the MgO inclusions were high, and at the same time, CaO inclusions, Al2O3 inclusions, and MnO-Cr2O3 inclusions were confirmed. As a result, the evaluation was fair.
[0077] Next, a comparative example will be described. No.15 had low Si. Conversely, Al was high and the CaO concentration in the slag exceeded the desired range, resulting in high Ca and Mg concentrations. As a result, MgO and CaO were not included in the average composition of the inclusions. The structure also had more f·CaO alone, with the CaO in the CaO-Al2O3-MgO oxides being high. In other words, the CaO alone inclusions became the center, causing defects and resulting in scrapping.
[0078] In No. 16, the Si concentration was too high, which resulted in high Ca and Mg concentrations. The high Si concentration also resulted in a high SiO2 concentration in the slag. The F concentration was also low, resulting in poor fluidity of the slag. The Ti concentration was also too high, resulting in the formation of TiN clusters. In the average composition of the inclusions, MgO and CaO were out of range, and alumina in the CaO-Al2O3-MgO oxide system, The contents of MgO and SiO2 were out of range, and the microstructure showed many f·CaO inclusions. The formation of many TiN and CaO inclusions caused many surface defects, resulting in the coils being scrapped.
[0079] In No.17, the Si content was low and Al was not included, which resulted in low Ca and Mg concentrations, and the oxygen concentration was high, resulting in a large number of non-metallic inclusions. In addition, the slag composition was also out of range, with high silica and low CaO, which had a negative effect on the inclusion composition. The average composition of the inclusions was out of range for all oxides, and the microstructure also showed the formation of many h·MnO-Cr2O3-based inclusions. Alumina and silica were also not included in the CaO-Al2O3-MgO-based oxide, and MnO-Cr2O3-based inclusions were confirmed. As a result, surface defects occurred along the entire length, resulting in scrapping.
[0080] No.18 had a high Al concentration, and the alumina concentration in the slag was high, while the CaO concentration was low. The average composition of the nonmetallic inclusions was 100% alumina, and the microstructure consisted of only g·Al2O3 inclusions. As a result, surface defects occurred along the entire length, causing scrapping.
[0081] No.19 had a low Al concentration, which resulted in low Ca and Mg concentrations and a high oxygen concentration, which was off the mark. The average composition of the nonmetallic inclusions was high in Cr2O3, and three types of structure were formed: f, g, and h. In particular, many h·MnO-Cr2O3-based inclusions were observed. Furthermore, MgO·Al2O3 simple inclusions and components that form a solid solution in MgO simple inclusions were off the mark. In addition, Ti and N concentrations were high, and TiN clusters were also observed. As a result, surface defects occurred along the entire length, causing scrapping.
[0082] In No. 20, the Ti and N values were too high, which caused many TiN clusters to form and surface defects, resulting in scrapping. In Table 2, all of the inclusion morphologies are a and b, which may seem good at first glance, but this is because TiN is not counted as an inclusion.
Claims
1. The alloy contains, in mass %, C: 0.001-0.1%, Si: 0.01-0.4%, Mn: 0.1-1%, P: 0.03% or less, S: 0.002% or less, Cr: 13-35%, Mo: 18% or less, W: 5% or less, Cu: 1% or less, Al: 0.001-0.35%, Ti: 0.001-0.2%, Ca: 0.0001-0.02%, Mg: 0.0001-0.02%, N: 0.001-0.03%, Fe: 2-11%, O: 0.005% or less, and one or more of Co, Nb and B in an amount of 4% or less, with the balance being Ni and unavoidable impurities. The average composition of the non-metallic inclusions is MgO: 30-70%, Al: 0.001-0.35%, Ti: 0.001-0.2%, Ca: 0.0001-0.02%, Mg: 0.0001-0.02%, N: 0.001-0.03%, Fe: 2-11%, O: 0.005% or less, and 4% or less of one or more of Co, Nb and B. 2 O 3 :15~40%, SiO 2 : 30% or less, CaO: 10 to 40%, MnO: 1% or less.
2. The Ni-based alloy having excellent surface properties according to claim 1, characterized in that the structural form of the non-metallic inclusions is such that 70% or more of the non-metallic inclusions in terms of number ratio to the total non-metallic inclusions are any one or more of the following five types a to e. a: CaO-Al 2 O 3 -MgO-based oxide is MgO.Al within the approximately spherical surface 2 O 3 A form that completely encompasses b: CaO-Al 2 O 3 -MgO acid compound c: CaO-Al 2 O 3 - A form in which MgO-based oxide completely encapsulates MgO within a substantially spherical surface d: MgO alone e: MgO.Al 2 O 3 Single
3. The CaO—Al 2 O 3 -MgO-based oxides are CaO: 20-60%, Al 2 O 3 :30~60%, MgO:1~30%, SiO 2 3. The Ni-based alloy having excellent surface properties according to claim 2, characterized in that: C: 20% or less, and TiO2: 0.5% or less.
4. The MgO.Al 2 O 3 The Ni-based alloy having excellent surface properties according to claim 2, characterized in that it contains 0.5% or less of MnO.
5. The MgO simple substance is Al 2 O 3 :3% or less, SiO 2 3. The Ni-based alloy having excellent surface properties according to claim 2, characterized in that it contains: 1% or less of Mo, 10% or less of CaO, and 1% or less of MnO.
6. A method for producing a Ni-based alloy according to any one of claims 1 to 5, comprising the steps of melting raw materials in an electric furnace, followed by decarburization and refining in an AOD, adding quicklime, magnesia-containing waste bricks, fluorite and ferrosilicon alloy, and one or more of Si and Al to carry out Cr reduction, and then adding Al to obtain CaO-Al 2 O 3 -MgO-SiO 2 A method for producing a Ni-based alloy with excellent surface properties, comprising forming an F-based slag, deoxidizing and desulfurizing the slab, producing a slab using a continuous casting machine, grinding the surface, subjecting the slab to a hot rolling process, and then performing cold rolling.
Citation Information
Patent Citations
JP1960-016661B
METHOD OF REFINING Ni BASED ALLOY HAVING EXCELLENT HOT WORKABILITY
JP2009114544A
Ni BASED ALLOY AND METHOD FOR MANUFACTURING THE SAME
JP2015183290A
Ni-based alloy products
JP4340899B2
High-strength Ni-based alloy tubes for nuclear power and methods for manufacturing the same
JP4433230B2